Intelligent Control of Switched Reluctance Motor for Electrical Vehicle Applications with Different Controller (Journal of University of Babylon for Engineering Sciences, 2023)
Switched reluctance motors (SRM) are used to produce a lot of torque when they are operating at high magnetic saturation. Due to the high magnetic saturation, the relationship between phase current, rotor position, and the flux linkage of SRM is nonlinear. Noise, disturbances, and inertia of load torque can all have a negative impact on the SRM driver system's speed controller performance. In this study, the SRM driver system's sliding mode controller was developed .The sliding mode controller( SMC) speed controller was used to regulate speeds of the SRM throughout a wide range speeds, including high and low speeds. This study compares (SMC) with a modified reaching law and a Proportional Integral Divertive Control (PID) controller for a 6/4 pole SRM using an optimization technique for switching controllers. Furthermore, the rotor speed was simulated and compared to the reference speed. The Exponential Sliding Mode Controller (ExpSMC) is the best in terms of performance and robustness for an electric vehicle application, depending on a simulation of an established test bench using the two controllers.